2018
DOI: 10.1016/j.ajog.2017.11.252
|View full text |Cite
|
Sign up to set email alerts
|

721: The Maternal-Infant Impactability Score™ (MIIS) identifies opportunity to reduce low birth weight through pregnancy care management

Abstract: preterm vs. term birth in the index twin pregnancy. The analysis was further stratified by gestational age at birth, indication for PTB and chorionicity in the index twin pregnancy. Unadjusted odds ratios and confidence intervals were calculated for each of the objectives. RESULTS: A total of 378 women met the study inclusion criteria, of whom 252 (66.7%) had PTB in the index twin pregnancy. The overall rate of PTB in the subsequent singleton pregnancy was 11.6% (44/378) and was significantly higher for women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In these studies, PTS regression analyses were performed using various sociodemographic factors, 26–28 30–32 health status (eg, presence of chronic conditions, prescription data, prior health resource utilisation and various health risk scores) 26–28 30–32 or previous programme engagement metrics. 28 One study found that high costs and high needs did not equate to high impactibility, as only small proportions of people with diseases that would be expected to have high burden had scores indicating high impactibility.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In these studies, PTS regression analyses were performed using various sociodemographic factors, 26–28 30–32 health status (eg, presence of chronic conditions, prescription data, prior health resource utilisation and various health risk scores) 26–28 30–32 or previous programme engagement metrics. 28 One study found that high costs and high needs did not equate to high impactibility, as only small proportions of people with diseases that would be expected to have high burden had scores indicating high impactibility.…”
Section: Resultsmentioning
confidence: 99%
“…Five of the identified studies reported the statistical validity of PTS models for projecting cost savings, improved engagement and/or care quality improvements; 26–28 30 32 however, prospective or comparative outcome data on the use of these models in real-world situations were extremely limited in the literature. Two studies reported improved engagement (defined as enrolment of contacted participants) with case management interventions after implementation of a PTS model: Ozminkowski et al 32 reported an 11% increase in programme enrolment in the 9 months after implementation of a PTS model, compared with the 3 months prior.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations